2000
DOI: 10.1002/(sici)1097-4628(20000411)76:2<228::aid-app12>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low molecular weight lactic acid derivatives on degradability of polylactide

Abstract: ABSTRACT:The presence of low molecular weight lactic acid derivatives in films enhanced the degradability of polylactide in a biotic medium. Two different biotic and abiotic series were investigated. The films used for the first abiotic and biotic series (a-1 and b-1 films) initially contained some lactic acid and lactoyl lactic acid, while the films used for the second abiotic and biotic series (a-2 and b-2 films) did not originally contain them. The b-1 films decreased in molecular weight during 3 weeks in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…10 It has been demonstrated that the easily assimilated lactic acid and lactoyl lactic acid formed during the degradation process promote the bio-degradation of PLA. 11 We have developed techniques to analyze and identify the hydrolysis products from aliphatic polyesters. 12,13 Despite the extensive data reported in the literature, some aspects of PLLA biodegradation are, however, still not completely understood.…”
Section: Introductionsupporting
confidence: 78%
“…10 It has been demonstrated that the easily assimilated lactic acid and lactoyl lactic acid formed during the degradation process promote the bio-degradation of PLA. 11 We have developed techniques to analyze and identify the hydrolysis products from aliphatic polyesters. 12,13 Despite the extensive data reported in the literature, some aspects of PLLA biodegradation are, however, still not completely understood.…”
Section: Introductionsupporting
confidence: 78%
“…[10] The other degradation products of PLA, i.e., ethyl ester of lactoyl lactic acid, propionic acid, and acetic acid, were also observed during aging with a mixed culture of microorganisms from compost. [20,21] The residual PLA films recovered from the culture broth may contain other cell lysis substances, such as a lipid layer of the cells released during chloroform extraction. However, the residual films were efficiently recovered by this extraction method.…”
Section: Degradation Of Pla Filmsmentioning
confidence: 99%
“…[3] The chemical properties of these polymers allow hydrolytic degradation through de-esterification. [4] The degradation occurs by uptake of water followed by the hydrolysis of the ester bonds. Several factors play role in the degradation kinetics of these polymers like the chemical composition, the molar mass, environmental conditions, the crystallinity, the hydrophobicity, etc.…”
Section: Introductionmentioning
confidence: 99%